The Role of the Village-Owned Enterprise of Kota Kandis Dendang Village in Community Economic Empowerment Based on Sharia Principles - Masyanto; Wargo; Dewi, Hasna; Arjmand, Reza (CV. Zabags Qu Publish, 2025)
This study explores the role of Village-Owned Enterprises (BUMDes) in promoting community economic empowerment in Kota Kandis Dendang Village through the application of Islamic economic principles. Despite the presence of various development programs initiated by BUMDes, public participation remains limited, largely due to low awareness and engagement. By adopting a qualitative field research approach using an empirical juridical method, the study collected primary data through observation, structured interviews, and documentation involving five key informants. The findings reveal four main themes: lack of community involvement, efforts to implement Sharia values, managerial and regulatory challenges, and emerging signs of social and economic empowerment. BUMDes has initiated inclusive programs that reflect Islamic ethical values, fostering trust and local support. However, structural constraints such as insufficient institutional capacity and absence of formal Sharia governance frameworks hinder its optimal implementation. This research contributes to the academic discourse by framing BUMDes as a hybrid institution economic and ethical rooted in religious values, and provides a practical reference for enhancing rural governance through Sharia-based models.